Effect of Alteplase Administration on International Normalized Ratio in Patients With Acute Ischemic Stroke. (July 2020) - Erdman, Michael J.; Davidson, K. Erin; Haller, J. Tyler; Shah, Samarth; Gross, Whitney; Andrews, Jessica; Patel, Alicia; Jones, G. Morgan
Background/Objective: Alteplase may elevate international normalized ratio (INR) results, although the exact rate of elevation occurrence is not firmly established in the literature. The purpose of this study is to determine the occurrence rate of INR elevation following alteplase administration. We also aimed to determine what factors are independently associated with the development of elevated INR following alteplase administration for ischemic stroke. Methods: We conducted a multicenter, retrospective, cohort study of patients who received alteplase for acute ischemic stroke. Patients were screened for baseline INR measurement and a repeat value within 24 hours of alteplase administration. The primary outcome was the percent of patients who experienced ≥0.4-point increase in INR. Secondary outcomes included the rate of adverse bleeding events and identification of factors independently associated with elevated INR following alteplase administration. Results and Conclusions: Two hundred and sixty-one patients were included, with 44 (16.9%) patients having an INR increase of 0.4 or more. Patients with an INR increase≥ 0.4 experienced a nonstatistically significant increase in bleeding episodes (8.8% vs 18.2%; P = .10). We identified African American race (odds ratio, 3.48, 95% confidence interval, 1.5-7.6; P = .002) as an independent predictor of INR increase ≥0.04. An INR elevation is common following receipt of alteplase for ischemic stroke. Those of African American race were at increased risk of INR elevation; however, more studies are needed to determine whether these patients are at a higher bleeding risk as a result of INR elevation.